Delineating genetic regulation of cannabinoid biosynthesis during female flower development in Cannabis sativa - Peter V. Apicella; Lauren B. Sands; Yi Ma; Gerald A. Berkowitz (Plant Direct, 2022)
Abstract Cannabinoids are predominantly produced in the glandular trichomes on cannabis female flowers. There is little known on how cannabinoid biosynthesis is regulated during female flower development. We aim to understand the rate‐limiting step(s) in the cannabinoid biosynthetic pathway. We investigated the transcript levels of cannabinoid biosynthetic genes together with cannabinoid contents during 7 weeks of female flower development. We demonstrated that the enzymatic steps for producing cannabigerol (CBG), which involve genes GPPS, PT, TKS, and OAC, could rate limit cannabinoid biosynthesis. Our findings further suggest that upregulation of cannabinoid synthases, CBDAS and THCAS in a commercial hemp and medical marijuana variety, respectively, is not critical for cannabinoid biosynthesis. The cannabinoid biosynthetic genes are generally upregulated during flower maturation; increased expression occurs coincident with glandular trichome development and cannabinoid production in the maturing flower. The results also suggest that different cannabis varieties may experience discrete transcriptional regulation of cannabinoid biosynthetic genes. In addition, we showed that methyl jasmonate (MeJA) can potentially increase cannabinoid production. We propose that biweekly applications of 100 μM MeJA starting from flower initiation would be efficacious for promoting cannabinoid biosynthesis. Our findings provide important genetic information for cannabis breeding to generate new varieties with favorable traits.